The Comparative Study between Speak Pal and Fully Fluent Application toward Students’ Speaking Skill - Novi Puji Lestari; Yayu Heryatun (Journal of Mandalika Literature, 2025)
This study aims to compare two mobile applications, Speak Pal and Fully Fluent, to evaluate their benefits towards EFL learners' speaking skills. Speak Pal connects users with native speakers worldwide, offering real-time conversation practice with various accents and dialects. Meanwhile, Fully Fluent utilizes an Artificial Intelligence (AI) tutor, "Fifi," to simulate native-speaker interactions, providing personalized feedback and practice across multiple languages. Moreover, this research employed qualitative descriptive techniques, involving observation and interviews with postgraduate student at the Islamic State University in Banten. Participants engaged in conversations using both applications to assess their fluency, comfort, and confidence. The findings reveal that Speak Pal offers more authentic interactions but can be challenging due to accent variability and limited free usage time. Fully Fluent, though less natural due to AI's robotic tone, supports users with text and audio aids, role-play scenarios, and adaptive learning paths, It is also often hindered by frequent advertisements in the free version. The study concludes that both applications have unique strengths and weaknesses. Speak Pal excels in providing real human interaction, which is crucial for advanced learners, while Fully Fluent offers structured practice and instant feedback, beneficial for building foundational speaking skills.